Merkel cell carcinoma. A review - Pink, Richard; Ehrmann, Jiri; Molitor, Martin; Tvrdy, Peter; Michl, Petr; Pazdera, Jindrich; Hanuliak, Jan (Biomedical papers, 2012)
Background: Merkel cell carcinoma (MCC) is a rare potentially fatal skin tumour affecting older mainly white people and younger immunosuppressed individuals. While uncommon, the incidence is increasing relative to melanoma and with twice the lethality. The benign appearance of the tumour usually on exposed skin parts, contrasting with its extensive microscopic invasion, can delay timely diagnosis. Recurrent MCC is currently attributed to the recently discovered Merkel cell polyomavirus This brief review of MCC covers the history, epidemiology,etiology,clinical and histological features, treatment and prognosis.Methods: Literature search using PubMed and search words Merkel cell carcinoma (MCC), etiology, treatment for the years 1972 to 2010.Results and conclusion. Merkel cell carcinoma is a rare malignancy with uncertain prognosis. Due to the uncommon occurrence and dearth of randomized studies, there is no agreement on optimal treatment. The tumor has only recently been included in the international classification of tumors (NCCN). The treatment approaches found to be best are radical surgery of primary tumor, drainage of lymph node extension and possibly adjuvant loco-regional radiotherapy. The basis of successful treatment however, remains prevention regular dermatological examination in immunosuppressed patients and early initiation of combination therapy, based on radical surgery supplemented by radiotherapy and palliative chemotherapy in the last resort.
Keywords: merkel cell carcinoma (MCC); etiology; treatment